Implementation of the Advanced Encryption Standard (AES) Algorithm on Access Code QR Codes in a Smart Door System - Ihsan Azhar Rhamadan; Kasliono; Syamsul Bahri (CV. Digital Innovation, 2025)
This research aims to design a smart door system based on QR codes with increased security using the AES-256-CBC algorithm. With AES-256-CBC encryption, the access code data sent from the device to the server is no longer in plaintext form, making it more secure from Man-in-the-Middle (MitM) attacks such as sniffing. The system utilizes ESP32-CAM to read QR codes and NodeMCU ESP32 to encrypt access data using a key hashed with SHA-256 and a 16-byte IV before being sent to the server for verification. Performance testing shows that the average delay increased from 66.4 ms to 67.46 ms after AES implementation, with a maximum value of 82 ms which is still in accordance with the TIPHON standard. On the throughput side, without AES the average is only 5.23 kbps due to shorter data, while with AES it increases to 7.30 kbps with a peak of 8 kbps due to the longer ciphertext size. The response time test recorded an average of 3830.76 ms and a maximum of 6086 ms, spanning the process from sending the code to opening the solenoid. Despite variations due to internet connection quality, delay spikes do not significantly impact system performance, indicating that the system remains secure and stable for IoT-based access control.